Supporting Student Success in the First-Year Experience: Library Instruction in the Learning Management System. Issue 1 (3rd April 2019) - Marineo, Francesca; Shi, Qingmin
Abstract: This article discusses how the Library and Office of Institutional Research at a public college measured the relationship of an online information literacy module in the learning management system with student success metrics in a first-year experience course. Specifically, the authors examine the relationships of an online instruction module, online module completion status, library use sessions, and student success metrics, such as semester grade point average (GPA), one-year retention, and academic standing. The results suggest that students who participated in the online information literacy module had better student outcomes than those that did not participate in the module. Research assignment grade and library use sessions are found as significant predictors of student semester GPA and one-year retention, controlling for high school GPA, student characteristics, and utilization of student support services. Practice implications are discussed.